Defect-mediated polarization switching in ferroelectric films for low-power-consuming and ultra-high-density memories. (9th May 2018) - Chen, Yingxin; Chen, Xin; Lu, Hongwei; Zhang, Lei; Yang, Yong; Shen, Qun-Dong
Abstract: Ferroelectric poly(vinylidene fluoride) (PVDF) based polymers are attracting tremendous interest because of their potential applications in flexible non-volatile memories. Current research suggests that the existence of a large hysteresis loop results in high-voltage operation and low writing/erasing speed, which is originated from uniform chain packing and coherent ferroelectric sequences in the crystalline regions. Here, we demonstrate the novel approach to understand the defect-mediated switching mechanisms in ferroelectric polymers by PFM-probe based technology. The single-point and linear polarization reversal is well controlled by defect-mediated ferroelectric phases that determine activation energy, switching rate, and the thermal stability. By the regulation of VDF/TrFE ratio and varying processing conditions, the coherent ferroelectric phase with all-trans sequence in the P(VDF-TrFE) has been disrupted by defects. Specially, the crystallites formed at high temperature in the copolymer P(VDF-TrFE) 50:50 mol% exhibit less ordered ferroelectric crystalline sequences, thus attaining the excellent features of the low operation voltage of about 4 V with a switching time of 100 ms, ultra-high memory density of 43.9 Gbit∙in −2 (by a 7 V, 1 ms pulse) and a high usage temperature of 60 °C. Compared with P(VDF-TrFE) 68:32 mol%, normal ferroelectric, it saves approximate 50% ratio of energy cost, and realizes four times higher resolution. Understanding and controlling defect functionality in ferroelectric materials is as critical for realizing their reliable applications in ferroelectric memories. Graphical abstract: Low-power-consuming, fast switching rate, and high usage temperature were attained in the defect-mediated P(VDF-TrFE) ultrathin films by using PFM testing. The excellent features in PVDF-based polymers can be potentially applied to many consumer electronics products, such as U-disk, CD-ROM, and digital versatile disks (DVD).Image 1 Highlights: Low operation voltage, fast switching, ultra-high memory density and high usage temperature are attained in P(VDF-TrFE) 50:50 mol%. The crystallites formed at high temperature in the copolymer P(VDF-TrFE) 50:50 mol% exhibit less ordered ferroelectric crystalline sequences.